2017
DOI: 10.1016/j.surg.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in patients with liver metastases from neuroendocrine tumors: A systematic review

Abstract: Liver transplantation may provide a survival benefit among patients with diffuse neuroendocrine tumors metastases to the liver. However, due to high recurrence rates, strict selection of patients is critical. Due to the scarcity of available grafts and the lack of level 1 evidence, the recommendations to endorse liver transplantation for extensive liver neuroendocrine tumors metastases warrants ongoing deliberations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 74 publications
(121 reference statements)
0
116
0
2
Order By: Relevance
“…Patients with unresectable disease may be considered for orthotopic liver transplantation, and a recent systematic review has detailed median 5-year OS of 63%, comparable to hepatocellular carcinoma [199]. Essentially all published studies have been retrospective in nature, and the selection criteria for transplantation are typically poorly described in many series, if at all [200].…”
Section: Surgical Management Of Nelmsmentioning
confidence: 99%
“…Patients with unresectable disease may be considered for orthotopic liver transplantation, and a recent systematic review has detailed median 5-year OS of 63%, comparable to hepatocellular carcinoma [199]. Essentially all published studies have been retrospective in nature, and the selection criteria for transplantation are typically poorly described in many series, if at all [200].…”
Section: Surgical Management Of Nelmsmentioning
confidence: 99%
“…With over 200 reported cases of pancreatoblastoma in the literature, we found no prior report of a successfully treated metastatic pancreatoblastoma by orthotopic liver transplant . While there is published experience in adults with metastatic neuroendocrine tumors of the pancreas using a similar strategy for staged procedures with liver transplantation for complete excision of disseminated liver metastatic disease, there is not a published experience of liver transplantation for this particular tumor, metastatic pancreatoblastoma . Salman et al have reviewed the very rare reported cases of pancreatoblastoma published in adults and their review does not include any cases of liver transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Moris and colleagues undertook a systematic review on the role of liver transplantation for NET–liver metastases . Liver resection with curative intent (R0/1 resection) was associated with long‐term survival benefit, but a higher incidence of recurrent metastatic disease.…”
Section: Liver Transplantationmentioning
confidence: 99%